Combining inhaled glucocorticoids and long acting β(2)-adrenoceptor agonists in asthma and COPD - Knox, A J (Nature Publishing Group, 2008)
Inhaled long-acting β(2)-adrenoceptor agonists and glucocorticoids form the mainstay of maintenance treatment of asthma and chronic obstructive pulmonary disease (COPD), usually given as a combination inhaler. Most patients will have good asthma control if they comply with this therapy, although it is generally less effective in COPD. The traditional dogma has been that these agents act on distinct components of disease pathophysiology with β(2) agonists acting on the bronchospastic component and glucocorticoids acting on the inflammatory component. Considerable evidence has emerged recently, however, to suggest that these two classes of agents interact at a molecular level. Understanding the mechanisms of these interactions may enable the development of new therapies for asthma and COPD.